Keputusan Penggunaan Quick Response Code Indonesian Standard (QRIS) Sebagai Alternatif Pembayaran Digital: di Solo Raya - Dinar Kurnia Setiyaningrum; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The use of Quick Response Code Indonesian Standard (QRIS) has experienced rapid growth. This study aims to analyze the factors influencing behavioral intention and use behavior of QRIS in Solo Raya. The variables examined include performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit. Primary data are collected from 181 respondents from an online questionnaire and analyzed using Partial Least Square (PLS). The results indicate that hedonic motivation and habit effect on behavioral intention, while behavioral intention has effect on use behavior. Other variables, performance expectancy, effort expectancy, social influence, facilitating conditions, and price value have no effect on behavioral intention. This study highlights that user enjoyment and habitual behavior are key factors in QRIS adoption in Solo Raya.